Late pulmonary metastasis in uterine PEComa. Issue 8 (30th July 2003) - Dimmler, A; Seitz, G; Hohenberger, W; Kirchner, T; Faller, G
Abstract : Perivascular epithelioid cell tumours (PEComas) other than angiomyolipoma, clear cell "sugar" tumour of the lung, and lymphangioleiomyomatosis are very rare mesenchymal tumours. The uterus seems to be the most prevalent site of involvement, but only 13 cases of uterine PEComa have been described. Three of these cases exhibited local aggressive behaviour and only one showed metastasis. Because of the extremely small number of cases, PEComas are considered tumours of uncertain malignant potential. This report describes a 68 year old woman, who presented with multiple pulmonary lesions seven years after the initial diagnosis of well differentiated endometrial stromal sarcoma. Histological and immunohistochemical analysis of the pulmonary lesions, in addition to re-evaluation of the primary uterine tumour, led to the final diagnosis of metastatic uterine PEComa. The findings indicate that any PEComa might have malignant potential. Spreading of this tumour to other organs might become evident even several years after primary manifestation.